2019
DOI: 10.1093/nar/gkz1023
|View full text |Cite
|
Sign up to set email alerts
|

LINCS Data Portal 2.0: next generation access point for perturbation-response signatures

Abstract: The Library of Integrated Network-Based Cellular Signatures (LINCS) is an NIH Common Fund program with the goal of generating a large-scale and comprehensive catalogue of perturbation-response signatures by utilizing a diverse collection of perturbations across many model systems and assay types. The LINCS Data Portal (LDP) has been the primary access point for the compendium of LINCS data and has been widely utilized. Here, we report the first major update of LDP (http://lincsportal.ccs.miami.edu/signatures) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
119
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(119 citation statements)
references
References 28 publications
0
119
0
Order By: Relevance
“…S 15b ). Investigation of the Library of Integrated Network-Based Cellular Signatures (LINCS) dataset 52 showed that compounds predicted to recapitulate the 3D tetra-culture signature included hypoxia inducible factor activators, caspase activators, and HDAC inhibitors, while RAF inhibitors and immunosuppressive agents may impair expression of this gene signature (Supplementary information, Fig. S 15c ).…”
Section: Resultsmentioning
confidence: 99%
“…S 15b ). Investigation of the Library of Integrated Network-Based Cellular Signatures (LINCS) dataset 52 showed that compounds predicted to recapitulate the 3D tetra-culture signature included hypoxia inducible factor activators, caspase activators, and HDAC inhibitors, while RAF inhibitors and immunosuppressive agents may impair expression of this gene signature (Supplementary information, Fig. S 15c ).…”
Section: Resultsmentioning
confidence: 99%
“…Hypergeometric overlap of the ACE2-correlated signature was performed via tools available through the National Institutes of Health Library of Integrated Network-Based Cellular Signatures. 20 Comparison with gene lists related to viral infection was accomplished using Enrichr 21 to interrogate the ''Virus Perturbations from GEO'' data set. Metadata from gene lists that demonstrated significant overlap with P value less than .05 after correction for multiple testing were mined for semantic similarity using hierarchical clustering based on cosine similarity measurement, identifying SARS-CoV as the most common term.…”
Section: Overlap With Library Of Integrated Network-based Cellular Simentioning
confidence: 99%
“…Recently, the next generation project of CMap was launched, termed the Library of Integrated Network-based Cellular Signatures (LINCS). 30,31) LINCS employs transcriptome profile data, although with added ingenuity to achieve high-throughput data acquisition. LINCS narrows target genes by data-driven analysis of 12063 transcriptome profile data points, so that the genes ultimately selected explain sufficient biological information about a specimen.…”
Section: Comparison Of Bridging Strategy Between a Disease And A Drugmentioning
confidence: 99%